PENGARUH LIKUIDITAS, KUPON, JANGKA WAKTU JATUH TEMPO DAN SUKU BUNGA PASAR TERHADAP HARGA PASAR OBLIGASI BERPERINGKAT RENDAH DAN HARGA PASAR OBLIGASI BERPERINGKAT TINGGI - Endri Purnomo; Novi Puspitasari (STIE Mandala Jember, 2017)
This paper aims to determine the effect of liquidity, coupon, maturity and market interest rates on the market price of low rated bonds and the market price of high rated bond. This study conducted on banking companies issuing bonds in the Indonesia Stock Exchange in the period 2011-2015. Low rated bonds taken out of bonds that are rated between A- to CCC as many as 52 sample data, while the high-rated bonds taken out of bonds that are rated AAA and AA + as many as 124 sample data. The method used in this research is multiple linear regression analysis. The results of partial testing showed that liquidity, coupon and maturity of no significant impact on the market price of low rated bonds. The same results were obtained on a partial test in high rated bonds, the liquidity and maturities have no significant impact on the market price of the high rated bond. however, the coupons have a significant effect on the market price of high rated bond. Variable market interest rate can not be processed because the data is constant so as not to do regression testing.